Ontology and Ethics - Ziziulas, John (Sabornost - The Theological Year-book, 2012)
Ethics as a term, in the Orthodox tradition, was something unknown. It is almost not at all found in the Fathers of the Church, and all up until recently it was not taught in schools either. In this paper we shall first try to clarify terminology. What do we mean when we talk about the ontology, and what when talking about ethics? In what follows we shall also explore the relationship between them within the Orthodox theology. Do ethics and ontology always dwell in harmony? Finally, we shall check to see how we can reach an ontological understanding of ethics in the light of the Gospel and Orthodox traditions.
Keywords: salvation; Church; ethos; Ethics; ontology